2002
DOI: 10.4049/jimmunol.169.2.633
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Targeted Ligation of CTLA-4 In Vivo by Membrane-Bound Anti-CTLA-4 Antibody Prevents Rejection of Allogeneic Cells

Abstract: Natural engagement of CTLA-4 on host B7 limits T cell activation. We hypothesized that therapeutic cross-linking of CTLA-4 in vivo may further inhibit T cell function and prevent allograft rejection. However, none of the currently available CTLA-4-binding reagents have ligating properties when injected in vivo. The observation that surface-immobilized anti-CTLA-4 mAb inhibits T cell activation in vitro prompted us to develop a membrane-bound single-chain anti-CTLA-4 Ab (7M). To model whether tissue expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 24 publications
4
32
0
1
Order By: Relevance
“…We have also shown that scaCTLA-4 can regulate CD8 + T cell-mediated tumor clearance in an in vivo tumor model (33). CD8 + T cells isolated from animals bearing scaCTLA-4 tumor cells were hyporesponsive ex vivo upon antigen rechallenge, indicating that CTLA-4 engagement resulted in tolerance (33). In this study, we have extended our previous findings to show that scaCTLA-4 expression on B cells inhibits CD4 + autoimmune responses in vivo.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We have also shown that scaCTLA-4 can regulate CD8 + T cell-mediated tumor clearance in an in vivo tumor model (33). CD8 + T cells isolated from animals bearing scaCTLA-4 tumor cells were hyporesponsive ex vivo upon antigen rechallenge, indicating that CTLA-4 engagement resulted in tolerance (33). In this study, we have extended our previous findings to show that scaCTLA-4 expression on B cells inhibits CD4 + autoimmune responses in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…In particular, we have previously shown that selective engagement of CTLA-4 using membrane-bound scaCTLA-4 inhibits antigenspecific T cell responses in vitro (18,20). We have also shown that scaCTLA-4 can regulate CD8 + T cell-mediated tumor clearance in an in vivo tumor model (33). CD8 + T cells isolated from animals bearing scaCTLA-4 tumor cells were hyporesponsive ex vivo upon antigen rechallenge, indicating that CTLA-4 engagement resulted in tolerance (33).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that ligation in cis is required for optimal CTLA-4 activity (18). The notion that CTLA-4 signaling can prevent rejection is supported by demonstration that expression of a single chain anti-CTLA-4 by transfected allogeneic tumor cells inhibits the anti-tumor response in immunodeficient hosts reconstituted with a limited number of TCR-tg CD8 cells (19). In the case of anti-CD45RB, a three-dose regimen capable of inducing short-term up-regulation of CTLA-4 at the time of transplantation actually promotes permanent engraftment and tolerance in immunocompetent, MHC disparate hosts (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Surface expression may decrease systemic side effects and more efficiently elicit the biological activities of proteins such as enzymes, single-chain antibodies (scFv) and cytokines. Several chimeric surface proteins have recently been described including chimeric scFv receptors for T-cell activation 15,[24][25][26] or deactivation, 27 membrane-bound cytokines, 28,29 prodrug-activating enzymes 30 and artificial Fc receptors. 31,32 Expression of engineered proteins on the surface of cells therefore represents a rich source for the development of novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%